Barriers to help-seeking for postpartum depression mapped onto the socio-ecological model and recommendations to address barriers - Place, Jean Marie S.; Renbarger, Kalyn; Van De Griend, Kristin; Guinn, Maya; Wheatley, Chelsie; Holmes, Olivia (Frontiers in Global Women's Health, 2024)
Postpartum depression affects nearly a quarter of women up to a year after childbirth. Although it is treatable, significant barriers to help-seeking prevent women from being treated. This paper assesses key literature on the barriers for help-seeking among women with postpartum depression. The barriers identified have been mapped onto the socio-ecological model in addition to potential recommendations that professionals can use to address barriers on individual, interpersonal, organizational, community and societal levels. The recommendations provided are meant to serve as leverage points for professionals in efforts to create appropriate support and interventions. As such, this paper serves as a mapping tool for healthcare and public health professionals to assess obstacles to women's help-seeking and to guide multi-pronged interventions on various levels of the socio-ecological model that may increase help-seeking among women with postpartum depression. Holistically and comprehensively providing support to women will require significant effort throughout all sectors of society as opposed to isolated, siloed interventions.